Analysis of the Risk Level of Work Accidents Using the Hirarc Method at PT. Inka Multi Solusi - Fauzia, Lavina Felda; Joumil Aidil Saifuddin Z.S (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
Occupational safety and health (K3) is something that needs to be considered by companies because it can affect the increasing effectiveness and productivity and can prevent things that can be detrimental from work accidents. Workers as one of the main resources in the running of the manufacturing industry, often experience health risks and occupational hazards such as minor accidents, and so on. At PT IMS itself, employees are very likely to experience work accidents that cause workers to be injured and production work time is reduced to lost due to these accidents because they are directly related to machines for production. By using the HIRARC method, it can be seen that of the 7 activities that have been identified in the metal production process at PT INKA Multi Solusi, there are 2 activities that fall into the moderate category, 2 activities that fall into the high category, and 3 activities that fall into the extreme category.